2020
DOI: 10.2147/ppa.s268499
|View full text |Cite
|
Sign up to set email alerts
|

<p>Impact of Medication Regimen Simplification on Medication Adherence and Clinical Outcomes in Patients with Long-Term Medical Conditions</p>

Abstract: Background This study aims to identify interventions used to reduce medication regimen complexity and to assess their impact on medication adherence and clinical outcomes. Methods A literature search was conducted using pre-defined search terms in three scientific databases, including ScienceDirect, ProQuest and MEDLINE. Original research articles published in English between 2009 and 2020 that assessed the impact of medication regimen simplification on medication adher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 50 publications
(175 reference statements)
1
20
0
1
Order By: Relevance
“…There a host of reasons to reduce polypharmacy in older adults, such as improving quality of life 29 and reducing the risk of adverse events. 30 Some reports have found that simplifying medication regimens does improve adherence (mostly in HIV infected adults), 31 but no regimen simplification interventions have been tested in people with COPD. Reducing complexity ought to be a goal of all clinicians when clinically indicated.…”
Section: Discussionmentioning
confidence: 99%
“…There a host of reasons to reduce polypharmacy in older adults, such as improving quality of life 29 and reducing the risk of adverse events. 30 Some reports have found that simplifying medication regimens does improve adherence (mostly in HIV infected adults), 31 but no regimen simplification interventions have been tested in people with COPD. Reducing complexity ought to be a goal of all clinicians when clinically indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Initially, and in contrast to the once-daily dosing of vadadustat [ 13 ], randomization to even twice weekly dosing has been reported with roxadustat [ 8 ]. There must be a pharmacodynamic reason for the thrice- or twice-weekly dose interval because it contrasts to the experience that medication adherence would be expected best with once-daily dosing [ 20 ]. However, in patients on hemodialysis, administration three times weekly would be suitable on the day of hemodialysis.…”
Section: Dosing and Formulationmentioning
confidence: 99%
“…Apart from these relatively special considerations, there is a generic need for community interventions to enforce a healthier lifestyle and pharmacotherapy optimization in most LMIC studies. Interventions that optimize pharmacotherapy which consider the simplifications of drug regimens are needed [ 66 ].…”
Section: Discussionmentioning
confidence: 99%